PERFORMANCE-BASED BUDGETING AND REGIONAL FINANCIAL PERFORMANCE: THE MODERATING ROLE OF LEADERSHIP COMMITMENT - Anton Robiansyah; Pesi Suryani (Jurnal Akuntansi, 2026)
This study aims to examine the effect of Performance-Based Budgeting (PBB) on Regional Financial Performance, with Leadership Commitment as a moderating variable. Evidence from the field indicates that although most local governments in Indonesia have formally adopted performance-based budgeting since the enactment of Government Regulation Number 12 of 2019 on Regional Financial Management, budget realization and value-for-money outcomes in numerous regions remain inconsistent, suggesting that formal adoption alone does not guarantee improved financial performance. This study employs a quantitative survey approach involving 180 respondents from budget and financial officers in Regional Apparatus Organizations (OPD), selected through purposive sampling. Data were analyzed using IBM SPSS Statistics through validity testing, reliability testing, classical assumption testing, multiple linear regression, and Moderated Regression Analysis (MRA). The results indicate that Performance-Based Budgeting has a positive and significant effect on Regional Financial Performance, and Leadership Commitment significantly strengthens this relationship. These findings reinforce Agency Theory and Stewardship Theory and offer practical implications for the Ministry of Home Affairs, the Ministry of Finance, and local governments in strengthening leadership commitment as a strategic lever for effective performance-based budget implementation.